Possibilities of conflict management using artificial intelligence in Latin American justice administration systems - Perilla Granados, Juan Sebastián Alejandro (2024)
Latin American justice administration systems operate within a changing global context characterized by dynamic technological transformations and the use of artificial intelligence. Although the legal profession has somewhat lagged in adopting these technological advancements, it is crucial to analyze, from ius-theoretical debates, the possibilities of implementing artificial intelligence in managing conflictive situations that require judicial intervention. Thus, it is possible to consider that artificial intelligence encompasses five levels of complexity, ranging from reactive systems to holistic models that have yet to be realized. Consequently, under current technological conditions, artificial intelligence could manage and resolve cases with low levels of complexity, while cases of advanced complexity still require human intervention. In this sense, this article provides a hermeneutic framework for understanding how to incorporate artificial intelligence at different levels into the management of cases with varying degrees of difficulty. To this end, it adopts a critical research approach, predominantly qualitative and grounded in documentary review.